O controle judicial de políticas públicas de saúde nas ações de natureza individual: possibilidade de coletivização da tutela individual pelo judiciário - Souza Filho, Sergio Murilo França de (2012)
The study proposal initially to analyze the constitutional role performed by the judiciary to intervene in the planning and execution of so-called Public Policy, aiming to ensure the full exercise and enjoyment of fundamental social rights in the constant search for common social good. Searching to elide the obstacle imposed on the judiciary in the exercise of the alluded control objective is to analyze the modern interpretation given to the theory of Separation of Powers, the result of the liberal state transition occurred for the welfare state, while the classical interpretation conceived by Montesquieu no longer holds the possibility of power intervention within the competence of another, giving rise to renewed discussion on the classical theory of Separation of Powers regarding the modern democracy. To deviate, still other obstacles imposed on the possibility of incursion the Judiciary in the formulation and execution of public policy, shall be analyzed the issue of the state's budget unavailability (possible reserves) and the legitimacy of this power to exercise judicial intervention also the criterion of injury or threat of injury to a minimum as an existential presupposed for judicial intervention on specific public policy. In the other hand, will be object for analyze the limits imposed by the doctrine and case law to exercise judicial review, running through the limits of reasonableness and subject to the reservation as possible. In order to provide an alternative to mass judicialization of the right to health in individual claims, whose individualized grant, result in the substantial violation of equality, will be the object to analyze the possibility of managing procedural instruments that have collective reach for granting universalized of this right, advising the possibility of a individual demand collectivization, using it as parameter the proposal bill that establishes a special procedure for the control and intervention in Public Policy by the Judiciary Power, developed by the Brazilian's Center of Judicial Studies and Research (CEBEPEJ).